Interferon alpha bioactivity critically depends on Scavenger receptor class B type I function. (2nd August 2016) - Vasquez, Marcos; Fioravanti, Jessica; Aranda, Fernando; Paredes, Vladimir; Gomar, Celia; Ardaiz, Nuria; Fernandez-Ruiz, Veronica; Méndez, Miriam; Nistal-Villan, Estanislao; Larrea, Esther; Gao, Qinshan; Gonzalez-Aseguinolaza, Gloria; et al.
ABSTRACT: Scavenger receptor class B type I (SR-B1) binds pathogen-associated molecular patterns participating in the regulation of the inflammatory reaction but there is no information regarding potential interactions between SR-B1 and the interferon system. Herein, we report that SR-B1 ligands strongly regulate the transcriptional response to interferon α (IFNα) and enhance its antiviral and antitumor activity. This effect was mediated by the activation of TLR2 and TLR4 as it was annulled by the addition of anti-TLR2 or anti-TLR4 blocking antibodies. In vivo, we maximized the antitumor activity of IFNα co-expressing in the liver a SR-B1 ligand and IFNα by adeno-associated viruses. This gene therapy strategy eradicated liver metastases from colon cancer with reduced toxicity. On the other hand, genetic and pharmacological inhibition of SR-B1 blocks the clathrin-dependent interferon receptor recycling pathway with a concomitant reduction in IFNα signaling and bioactivity. This effect can be applied to enhance cancer immunotherapy with oncolytic viruses. Indeed, SR-B1 antagonists facilitate replication of oncolytic viruses amplifying their tumoricidal potential. In conclusion, SR-B1 agonists behave as IFNα enhancers while SR-B1 inhibitors dampen IFNα activity. These results demonstrate that SR-B1 is a suitable pharmacology target to enhance cancer immunotherapy based on IFNα and oncolytic viruses.